DECOLORIZATION OF AZO DYES AND MINERALIZATION OF PHENANTHRENE BY TRAMETES SP. AS03 ISOLATED FROM INDONESIAN MANGROVE FOREST - Hidayat, Asep; Tachibana, Sanro (Indonesian Journal of Forestry Research, 2014)
Textile industry contributes the most disposals of synthetic dyes, and about 40% of textile dyes has been generating high amount of colored wastewater. Polycyclic aromatic hydrocarbons (PAHs), such as phenanthrene, is a group of organic compounds, that structurally comprised of two or more benzene rings, which persist in air, water, and soil. The organic pollutants of dyes and PAHs have adversely effects the food chain and are potentially toxic, mutagenic, and carcinogenic to the environment. The objective of this research is to screen and investigate the potential fungus from mangrove forest to degrade azo dyes and phenanthrene.Â  In this study, fungi were collected from mangrove forest in Riau Province â Sumatra â Indonesia. Previously, Trametes sp. AS03 is one of the fungi isolated from mangrove forest in Riau Province, that was able to decolorize Remazol Brilliant Blue R (RBBR). The capability of Trametes sp. AS03 to decolorize four azo dyes, Remazol B. Violet (V5), Levafix Orange E3GA (Or64), Levafix B. Red E-6BA (R159), and Sumifix S. Scarlet 2GF (R222), were further evaluated. The result shows that Trametes sp. AS03 decolorized 91, 60, 48, and 31 of V5, R222, R159, and Or64, respectively. By showing its capability to decolorize some of the dyes, Trametes sp. AS03 was used to break down phenanthrene. AS03 degraded more than 70% of phenanthrene in 15 days.